We Are One: Multispecies Metabolism of a Biofilm Consortium and Their Treatment Strategies - Joshi, Ruchika Vinod; Gunawan, Cindy; Mann, Riti (Frontiers in Microbiology, 2021)
The ecological and medical significance of bacterial biofilms have been well recognized. Biofilms are harder to control than their planktonic free-living counterparts and quite recently, the focus of the study has shifted to the multispecies consortia, which represent the vast majority of real-case infection scenarios. Studies have begun to explore the complex interspecies interactions within these biofilms. However, only little attention is currently given to the role of cellular metabolites in the cell-to-cell communication. The concentration gradients of metabolic substrates and products affect the spatial growth of bacteria in multispecies biofilm. This, if looked into more deeply, can lead to identification of potential therapies targeting the specific metabolites and hence the coordinated protection in the bacterial community. Herein, we review the interspecies communications, including their metabolic cross-talking, in multispecies biofilm, to signify the importance of such interactions on the initial formation and subsequent growth of these biofilms. Multispecies biofilms with their species heterogeneity are more resilient to antimicrobial agents than their single species biofilm counterparts and this characteristic is of particular interest when dealing with pathogenic bacteria. In this Review, we also discuss the treatment options available, to include current and emerging avenues to combat pathogenic multispecies biofilms in the clinical, environmental, as well as industrial settings.